PARAMETER EQUIVALENT METHOD OF STATOR ANISOTROPIC MATERIAL BASED ON MODAL ANALYSIS - TANG YouLiang; LV PinDe; ZHANG Jin; LI ShouJun (Jixie qiangdu)
Accurate calculation of the mode shape and natural frequency of the motor stator is the basis for reducing motor noise and vibration. At present, scholars have disputes about the setting of stator core and winding material property parameters. In this paper, the modal simulation analysis and experimental test of a 2.2 kW permanent magnet brushless DC motor stator system are carried out. First, to give the stator core and the winding materials, The finite element software is used to analyze the relationship between the motor modal frequency and the parameters of the anisotropic materials. According to the modal frequency variation law, a method for correcting the parameters of the anisotropic materials based on the modal frequency is proposed. The method can complete the finite element model parameter correction of the stator. Secondly, the modal experiment is carried out by hammering method to verify the accuracy of the finite element model and determine the effectiveness of the method for correcting the equivalent material parameters. And by this method, the stator material parameters of the stator can be quickly determined. The error of this experiment and simulation is within 3%, achieving the purpose of experiment and simulation benchmarking.